Catalogue of the Byzantine coins in the Dumbarton Oaks Collection and in the Whittemore Collection. Vol. IV : Alexius I to Michael VIII, 1081-1261. Pt. 2 : The Emperors of Nicaea and their Contemporaries, 1204-1261. - Hendy, Michael F. (Washington)
vi, s. [447]-736, liv s. res.